CONSUMER ETHNOCENTRISM EXPLORATION OF BRAND VALUE, BRAND IMAGE, AND PRODUCT BUYING INTENTION INDONESIAN LOCAL FASHION IN GEN Z MEDAN CITY - Achmad Afriadi Trisatya; Yeni Absah; Beby Karina F. Sembiring (CV. Radja Publika, 2023)
This study aims to analyze how consumer ethnocentrism affects brand value, brand image, and the purchase intention of local Indonesian fashion products among Gen Z in the city of Medan. The type of research conducted is quantitative descriptive research. The population in this study is the Gen Z community in Medan city, with a sample of 150 respondents. The sample size was determined using the purposive sampling method. This research uses structural equation modeling (SEM) with the analysis tool SmartPLS version 3.0. The direct results of the research show that consumer ethnocentrism has a positive and significant impact on brand value; consumer ethnocentrism has a positive and significant impact on brand image; then consumer ethnocentrism has a positive but not significant impact on purchase intention. then, brand value has a positive but not significant impact on the purchase intention, however, brand image has a positive and significant impact on the purchase intention. Furthermore, indirect testing results reveal that brand value is not able to mediate the relationship between consumer ethnocentrism and the purchase intention, but brand image is able to mediate the relationship between consumer ethnocentrism and the purchase intention.